Pamięć konstruowana : Żołnierze Wyklęci w narracjach polskich tygodników opinii (Politeja, 2020)
Built Memory. ‘Cursed Soldiers’ in the Narratives of Polish Opinion-Forming WeekliesThe activity of the anti-communist underground was for many years a marginalised element both in historical education and public discourse. However, we have noticed a significant turn in this matter recently. This process is manifested by specific ‘acts of remembrance,’ such as honorary funerals of the exhumed cursed soldiers’ bodies. What is crucial is that in the background we can observe an extremely important action of constructing memory about the activists of the Polish underground, in which several separate narratives can be distinguished. Mass media play a key role in this process. They create interpretative schemes using among others the ‘post-memory’ testimonies and influence on constructing social memory and post-memory itself. The aim of this article is to recreate interpretative schemes concerning the life and activity of the cursed soldiers in the following Polish weeklies: Gość Niedzielny, Polityka, Newsweek Polska and wSieci. My selection was determined by their current sales results. The method used in the study is framing analysis.